Determinants of youth demand for healthcare facilities in Seri Iskandar / Muhammad Adib Hafizi Mohd Khiri - Mohd Khiri, Muhammad Adib Hafizi (2023)
The determinants for healthcare facilities are related to a person's health status and income. As Seri lskandar is the educational hub of Perak, most of the youth's income level in Seri lskandar is not adequate to obtain healthcare services from private healthcare facilities. Although several studies have been developed to identify the determinants of the elderly group, disabled and general population towards healthcare facilities, youth with different lifestyles and environments between areas will create varied determinants. Hence, this study was set out to analyse the existing literature on the determinants in the perspectives of youth groups in Seri lskandar. The PRISMA review method had resulted in five main determinants factor, they were healthcare distance factor, duration of medical examination, medical cost, healthcare services provided and adoption of types of healthcare technologies. For further research, these four themes could contribute to the development of a comprehensive development plan for holistic healthcare facilities.